Implementasi Pendekatan Saintifik Terhadap Prestasi Belajar IPA Ditinjau dari Minat Outdoor - Made Sri Astika Dewi (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2019)
This research headed to know the influences of scientific approach for natural science learning  achievement reviewed from outdoor interest. This research used factorial control group design with pseudo-experiments. There were 129 research samples.  The population of this study is all students of fifth grade of Elementary School Gugus III Negara Sub-district with amount to 211 students. The sample in this research was done by random sampling technique, with 67 students of experimental group and 62 control group students. The data were about students’ outdoor interest and students’ natural science learning  achievement by using learning  achievement test. The data analyzed by ANAVA with two lines and SPSS 16.00 for windows. The research result indicated: first, the difference between students’ learning  achievement who following the learning process with scientific approach was better than following learning process with conventional approach (F = 31,269; p< 0,05), second, there were the influences between students’ interaction with scientific approach and outdoor interest to learning  achievement(F = 10,799; p< 0,05). Third, there were differences between student who followed learning process with scientific approach and students who followed learning process with conventional approach for the students who had high outdoor interest (t = = 6,233; p< 1,984). There were not differences between student who followed learning process with scientific approach and students who followed learning process with conventional approach for the students who had low outdoor interest (t = 1,64; p< 1,984)